Global Solution for the Generalized Anisotropic Navier–Stokes Equations with Large Data - Fang, Daoyuan; Han, Bin (Mathematical Modelling and Analysis, 2015)
We are concerned with 3D incompressible generalized anisotropic Navier– Stokes equations with hyperdissipative term in horizontal variables. We prove that there exists a unique global solution for it with large initial data in anisotropic Besov space.